Metal organic framework material, preparation method thereof and perovskite battery
By using metal organic frame material UiO-66-2H nanoparticles in the hole transport layer of perovskite solar cells to adsorb and disperse lithium ions, the perovskite layer degradation problem caused by lithium ion migration is solved, and the stability and performance of the battery are improved.
Patent Information
- Application Number
- CN202411970988.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-15
AI Technical Summary
In existing perovskite solar cells, Li+ in the dopant is easily migrated to other layers, resulting in the degradation of the perovskite layer and affecting the stability of the battery.
UiO-66-2H nanoparticles are used as part of the hole transport layer, and lithium ions are adsorbed through high-density free carboxyl groups and uniformly dispersed through the nanostructure to prevent lithium ions from migration.
Effectively prevent lithium ions from migrating to the perovskite active layer, reduce the degradation of the perovskite layer, and improve the electrochemical performance and stability of perovskite batteries.
Smart Images

Figure CN119823402A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite cells, and in particular to a metal organic framework material and a preparation method thereof, and a perovskite cell. Background Art
[0002] Perovskite solar cells (PSCs) have attracted widespread attention due to the rapid improvement in power conversion efficiencies (PCEs) in the past few years. The currently certified highest device efficiency has exceeded 26%, comparable to mainstream crystalline silicon solar cells. Moreover, compared with crystalline silicon cells, the cost of raw materials required to manufacture PSCs is relatively low, and the manufacturing process is relatively simple, so the production cost is low, which is expected to reduce the overall cost of solar cell systems.
[0003] Perovskite solar cells have a sandwich structure consisting of a perovskite layer between an electron transport layer (ETL) and a hole transport layer (HTL). Among them, using a suitable HTL to effectively extract holes and protect the inner perovskite is the key to improving the performance of perovskite solar cells. For example, in formal (nip) PSCs, the organic small molecule Spiro-OMeTAD is mainly used as a hole transport layer, but the hole mobility of Spiro-OMeTAD alone is low, and some dopants / additives (lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) and 4-tert-butylpyridine (tBP)) are usually required to improve the conductivity and mobility to obtain high-performance perovskite solar cells. However, the residual Li in the dopant + It is easy to migrate from the hole transport layer to other layers, and it is also sensitive to humidity and heat. It is easy to absorb water from the environment when left for a long time, resulting in accelerated degradation of the perovskite layer, which will have a negative impact on the stability of the perovskite solar cell device. Summary of the invention
[0004] Based on the background technology, the main purpose of the present invention is to provide a metal organic framework material and a preparation method thereof and a perovskite battery.
[0005] To achieve the above object, the present invention provides a method for preparing a metal organic framework material, comprising the following steps:
[0006] 1,2,4,5-benzenetetracarboxylic acid is dissolved in an organic solvent, ZrCl4 and a regulator acetic acid are added, and the mixture is heated for reaction to obtain a reactant, and the reactant is centrifuged, washed, and dried to obtain UiO-66-2H nanoparticles.
[0007] In some embodiments of the present invention, the amount of the regulator acetic acid added is 20-100 uL; and / or the mass ratio of 1,2,4,5-benzenetetracarboxylic acid and ZrCl4 is (1:2) to (1:4).
[0008] In some embodiments of the present invention, the temperature of the heating reaction is 80° C. to 120° C.; and / or the reaction time of the heating reaction is 12 h to 24 h.
[0009] The present invention also provides a metal organic framework material prepared by the method for preparing the metal organic framework material as described above.
[0010] In some embodiments of the present invention, the metal organic framework material includes free carboxyl groups.
[0011] The present invention also provides a perovskite cell, which comprises a hole transport layer, and the hole transport layer comprises the metal organic framework material as described above.
[0012] In some embodiments of the present invention, the perovskite cell comprises, from bottom to top, a conductive substrate, an electron transport layer, a perovskite active layer, the hole transport layer and a back electrode layer.
[0013] In some embodiments of the present invention, the method for preparing the hole transport layer comprises the following steps:
[0014] The hole transport layer material and the metal organic framework material are mixed and dissolved to obtain a hole transport layer solution,
[0015] The hole transport layer is obtained by coating the hole transport layer solution on the surface of a substrate.
[0016] In some embodiments of the present invention, the mass ratio of the hole transport material to the metal organic framework material is (100:1) to (50:1).
[0017] In some embodiments of the present invention, the hole transport layer solution further includes a dopant, and the dopant includes a lithium ion dopant.
[0018] The beneficial effects that can be achieved by the present invention are:
[0019] The present invention mixes 1,2,4,5-benzenetetracarboxylic acid and ZrCl4, and adds acetic acid as a regulator, so as to regulate the crystal growth of the metal organic framework material, and prepares the metal organic framework material UiO-66-2H nanoparticles with high-density free carboxyl groups and nanostructures. The high-density free carboxyl groups can help the UiO-66-2H nanoparticles to adsorb lithium ions, and the nanostructures can help the UiO-66-2H nanoparticles to obtain better dispersibility.
[0020] UiO-66-2H nanoparticles are used to prepare the hole transport layer of perovskite batteries. The high-density free carboxyl groups of UiO-66-2H nanoparticles can adsorb lithium ions well, preventing the lithium ions in the hole transport material and / or the hole transport layer from migrating to the perovskite active layer. UiO-66-2H nanoparticles can also be evenly dispersed in the hole transport material by virtue of their nano-morphology, thereby better adsorbing lithium ions in the solution and preventing lithium ions from migrating to the perovskite active layer and accelerating its degradation. In addition, the free carboxyl groups in the UiO-66-2H nanoparticles can also form chemical bonds with the pb ions in the perovskite active layer, reducing the surface defects and unsaturated bonds of the perovskite active layer, preventing the recombination of electrons and holes, and thus improving the electrochemical performance and stability of the perovskite battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0022] Figure 1 This is a morphology diagram of UiO-66-2H nanoparticles according to an embodiment of the present invention.
[0023] Figure 2 This is the PXRD diffraction pattern of UiO-66-2H nanoparticles in Example 1 of the present invention.
[0024] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0025] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] In the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0028] The present invention provides a metal organic framework material and a preparation method thereof, the preparation method comprising the following steps:
[0029] 1,2,4,5-benzenetetracarboxylic acid is dissolved in an organic solvent, ZrCl4 and a regulator acetic acid are added, and the reaction is heated to obtain a reactant. The reactant is centrifuged, washed, and dried to obtain UiO-66-2H nanoparticles. The obtained UiO-66-2H nanoparticles are metal organic framework materials.
[0030] In some embodiments, ZrCl4 is dispersed in an organic solvent to obtain a ZrCl4 solution, 1,2,4,5-benzenetetracarboxylic acid is dispersed in an organic solvent to obtain a 1,2,4,5-benzenetetracarboxylic acid solution, and then the ZrCl4 solution and the 1,2,4,5-benzenetetracarboxylic acid solution are mixed to obtain a reaction solution.
[0031] In some embodiments, the organic solvent for dispersing ZrCl4 includes N,N-dimethylformamide (DMF).
[0032] In some embodiments, the organic solvent for dispersing 1,2,4,5-benzenetetracarboxylic acid includes N,N-dimethylformamide (DMF).
[0033] In some embodiments, a reaction vessel with a polytetrafluoroethylene liner can be selected to disperse ZrCl4 and 1,2,4,5-benzenetetracarboxylic acid and perform the reaction.
[0034] In some embodiments, ZrCl 4 is added to an organic solvent, and the dissolution and dispersion of ZrCl 4 is promoted by ultrasound to obtain a ZrCl 4 solution.
[0035] In some embodiments, 1,2,4,5-benzenetetracarboxylic acid is added to an organic solvent, and ultrasound is used to promote the dissolution and dispersion of 1,2,4,5-benzenetetracarboxylic acid to obtain a 1,2,4,5-benzenetetracarboxylic acid solution.
[0036] In some embodiments, the mass ratio of 1,2,4,5-benzenetetracarboxylic acid to ZrCl4 is (1:2) to (1:4), and can be 1:2, 1:3, 1:4, etc.
[0037] In some embodiments, the amount of the regulator acetic acid added is 20-100 uL. In this embodiment, by adding acetic acid, the crystal growth of UiO-66-2H nanoparticles can be adjusted, the UiO-66-2H nanoparticles can be prompted to obtain high-density free carboxylic acids, and the nanostructure can be controlled.
[0038] In some embodiments, the temperature of the heating reaction is 80°C to 120°C, for example, it can be any value in the range of 80°C to 120°C, such as 80°C, 90°C, 100°C, 110°C, 120°C, etc.
[0039] In some embodiments, the reaction time of the heating reaction is 12 h to 24 h. For example, it can be any value within the range of 12 h to 24 h, such as 12 h, 15 h, 18 h, 20 h, 22 h, 24 h, etc.
[0040] After the reaction is completed, the mixture is cooled to room temperature, and the reactant is taken out and centrifuged at a speed of 6000 to 10000 rpm to collect the precipitate, which contains the target product.
[0041] In some embodiments, the precipitate collected by centrifugation is washed to remove impurities, and the detergents used for washing include deionized water, N,N-dimethylformamide, and ethanol. For example, deionized water, N,N-dimethylformamide, and ethanol can be used in sequence for washing, which is conducive to removing most of the impurities.
[0042] In some embodiments, the method of drying comprises vacuum drying.
[0043] The UiO-66-2H nanoparticles prepared by the present invention are in solid state and easy to store.
[0044] The present invention mixes 1,2,4,5-benzenetetracarboxylic acid and ZrCl4, and adds acetic acid as a regulator, so as to regulate the crystal growth of the metal organic framework material and prepare UiO-66-2H nanoparticles with high-density free carboxyl groups and nanostructures. The high-density free carboxyl groups can help the UiO-66-2H nanoparticles to adsorb lithium ions, and the nanostructures can help the UiO-66-2H nanoparticles to obtain better dispersibility.
[0045] Therefore, the present invention further provides an application of a metal organic framework material, specifically, provides a perovskite cell, the perovskite cell comprises a hole transport layer, and the hole transport layer contains the metal organic framework material UiO-66-2H nanoparticles of the present invention as described above.
[0046] The present invention applies metal organic framework material UiO-66-2H nanoparticles to prepare the hole transport layer of the perovskite battery. The high-density free carboxyl groups of the UiO-66-2H nanoparticles can well adsorb lithium ions, prevent the lithium ions from migrating to the perovskite active layer and accelerating the degradation of the perovskite active layer. The UiO-66-2H nanoparticles can also be evenly dispersed in the hole transport material by virtue of their nano-morphology, thereby better adsorbing lithium ions in the solution. In addition, the free carboxyl groups in the UiO-66-2H nanoparticles can also form chemical bonds with the Pb ions of the perovskite active layer, reduce the surface defects and unsaturated bonds of the perovskite active layer, prevent the recombination of electrons and holes, improve the photoelectric performance of the perovskite material, and thus improve the electrochemical performance of the perovskite battery.
[0047] In some embodiments, the perovskite cell includes a formal perovskite cell, which includes a conductive substrate, an electron transport layer, a perovskite active layer, the hole transport layer and a back electrode from bottom to top. In this embodiment, a functional layer commonly used in the art may be provided between the conductive substrate and the electron transport layer, between the electron transport layer and the perovskite active layer, and between the hole transport layer and the back electrode to improve the performance of the perovskite cell. For example, a passivation layer may be provided between the hole transport layer and the back electrode.
[0048] In some implementations, the material for preparing the passivation layer includes an isopropyl alcohol (IPA) solution of phenethylammonium iodide (PEAI), and interface defects are reduced by preparing the passivation layer.
[0049] In some embodiments, a buffer layer may also be provided, which may improve interface modification, optimize energy levels, and prevent metal corrosion.
[0050] In the present invention, the conductive substrate, electron transport layer, perovskite active layer and back electrode layer of the perovskite battery can be prepared by selecting materials commonly used in the art.
[0051] Regarding the conductive substrate, illustratively, the preparation of the conductive substrate includes: ultrasonically washing the conductive substrate with a cleaning agent Hellmanex aqueous solution, deionized water, acetone and isopropyl alcohol (IPA), respectively, and then blowing it dry with N2 for standby use, and then placing it in a UVO cleaning machine, and oxidizing and removing grease and organic matter on the surface of the substrate by ultraviolet light and ozone to achieve a cleaning effect. At the same time, the hydrophilicity and hydrophobicity of the conductive substrate can also be changed, and the wettability of the conductive substrate can be improved.
[0052] Regarding the electron transport layer, illustratively, the electron transport layer can be prepared by chemical vapor deposition, electrochemical deposition, physical epitaxial growth, thermal evaporation, atomic layer deposition, precursor liquid slit coating, precursor liquid doctor blade coating, sol-gel method, magnetron sputtering, pulsed laser deposition, etc. In this embodiment, the electron transport layer material includes at least one of TiO2, ZnO, SnO2, PCBM, PCBA, and PEN.
[0053] Regarding the perovskite active layer, illustratively, before depositing the perovskite layer, a conductive substrate prepared with a functional layer, such as a FTO / SnO2 substrate prepared with SnO2, is placed in a UVO cleaning machine. UVO cleaning for 5 to 15 minutes can allow the perovskite solution to spread better on the substrate.
[0054] In some embodiments, the perovskite solution includes a mixed solution of MDF / DMSO containing different proportions of PbI2, FAI, MACl and MAPbBr3. In addition, different perovskite components can be added to adjust the performance of the battery, including but not limited to MABr, CsI, MAI, PbBr2.
[0055] In some embodiments, the perovskite active layer is prepared by spin coating. For example, the perovskite solution is spin coated onto the electron transport layer of the FTO / SnO2 substrate, and then annealed at 100° C. to 150° C. for 1 h to obtain the perovskite active layer.
[0056] Regarding the back electrode, the back electrode includes a metal electrode. The material of the back electrode can be deposited on the surface of the substrate by methods such as magnetron sputtering. The material of the back electrode includes metals or metal alloy materials such as Mo, Al, Au, Ag, Cu, Ni, and Cr.
[0057] In some embodiments, the method for preparing the hole transport layer comprises the following steps:
[0058] S10, mixing and dissolving the hole transport layer material and the metal organic framework material to obtain a hole transport layer solution,
[0059] S20, coating a hole transport layer solution on the surface of the substrate to obtain a hole transport layer.
[0060] In some embodiments, the mass ratio of the hole transport material to the metal organic framework material is (100:1) to (50:1), which can be 100:1, 80:1, 60:1, 50:1, etc. Under the above ratio conditions, UiO-66-2H can adsorb free Li ions to the greatest extent without causing agglomeration in the hole transport layer, such as the Spior-OMeTAD film layer, which affects the uniformity of the film layer.
[0061] In some embodiments, the hole transport layer material includes common materials in the art, and different hole transport layer materials can be selected according to the type of perovskite, the hole transport layer material is dissolved and dispersed in a solvent, and the metal organic framework material is added as a hole transport layer material additive, and mixed and dispersed to prepare a hole transport layer solution. The metal organic framework material has a nanostructure and can be well dispersed in the hole transport material to prepare a hole transport layer, and can be evenly distributed in the hole transport layer to achieve a good lithium ion adsorption effect.
[0062] In some embodiments, the hole transport material includes 2,2′,7,7′-tetrakis(N,N-di-4-methoxyphenylamino)-9,9′-spirobifluorene (Spiro-OMeTAD). Spiro-OMeTAD is dispersed in a solvent, and a metal organic framework material is added and mixed and dispersed to obtain a hole transport layer solution. The hole transport layer solution of this embodiment can be used to prepare a formal perovskite cell.
[0063] In some embodiments, a dopant may also be added to the hole transport layer solution, and the dopant may include a lithium ion dopant. Exemplarily, the lithium ion dopant includes lithium bis(trifluoromethylsulfonyl)imide (Li-TFSI). In the present embodiment, the hole transport layer solution contains a lithium ion dopant, and lithium ions easily migrate to the perovskite active layer to cause the degradation of the perovskite. After adding the organic framework material UiO-66-2H nanoparticles, the above problems can be effectively solved. The free carboxyl groups in the UiO-66-2H nanoparticles can capture lithium ions, and the nanostructure of the UiO-66-2H nanoparticles can also promote their uniform dispersion in the hole transport layer solution, so that the lithium ions in the solution can be fully captured, and the migration of lithium ions to the perovskite active layer is inhibited.
[0064] In some embodiments, other dopants in the art may be added to the hole transport layer solution. For example, the dopant may include a cobalt (III) complex (FK209).
[0065] In some embodiments, the hole transport material can be dissolved in an organic solvent, and UiO-66-2H nanoparticles can be added, and the UiO-66-2H nanoparticles can be evenly distributed in the hole transport layer solution by ultrasound. Exemplarily, the organic solvent includes chlorobenzene, and the UiO-66-2H nanoparticles can be evenly dispersed in chlorobenzene.
[0066] In the present invention, the addition of dopants can refer to the methods commonly used in the art. For example, other dopants such as lithium ion dopants can be dissolved in organic solvents such as acetonitrile and then added to the hole transport layer solution, which is beneficial to the dispersion of lithium ion dopants and facilitates the capture of lithium ions by UiO-66-2H nanoparticles.
[0067] In some embodiments, 80 μl to 150 μl of the hole transport layer solution can be drawn and applied to the surface of the substrate to form a hole transport layer, thereby obtaining a hole transport layer of moderate thickness. It is understood that the amount can be any amount within the range of 80 μl to 150 μl, such as 80 μl, 100 μl, 120 μl, 130 μl, 140 μl, 150 μl, etc.
[0068] In some embodiments, the hole transport layer can be prepared on the surface of the substrate by spin coating, and the spin coating conditions include: spin coating at a rotation speed of 4000 rpm and an acceleration of 2000 rpm / s for 30 seconds.
[0069] In the present invention, the substrate of step S20 can be determined according to the structure of the perovskite cell. For example, the perovskite cell is a formal perovskite cell, which includes a conductive substrate, an electron transport layer, a perovskite active layer, a hole transport layer and a back electrode layer from bottom to top. The substrate of this embodiment is the perovskite active layer.
[0070] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following specific embodiments are only used to explain the present invention, and are not used to limit the present invention.
[0071] Example 1
[0072] Preparation of metal organic framework material UiO-66-2H nanoparticles:
[0073] Weigh 10 mg of ZrCl4 in a 10 mL reagent bottle, add 2 mL of DMF and ultrasonically dissolve to obtain a ZrCl4 solution, and use a rubber-tipped pipette to suck the ZrCl4 solution into a 20 mL polytetrafluoroethylene liner;
[0074] 5 mg of 1,2,4,5-benzenetetracarboxylic acid was weighed and added to 2 mL of DMF for ultrasonic dissolution to obtain a 1,2,4,5-benzenetetracarboxylic acid solution, which was sucked into a polytetrafluoroethylene liner containing a ZrCl4 solution using a rubber-tipped pipette, and 20 μL of acetic acid was added as a regulator. The reaction vessel was placed in a reactor, which was placed in an oven and heated at 80°C for 24 hours to obtain a reactant. The reactant was taken out, cooled, and centrifuged at a speed of 6000 rpm to 10000 rpm to collect the solid product, which was washed with deionized water, DMF, and ethanol, respectively, and then vacuum-dried to obtain metal organic framework material UiO-66-2H nanoparticles.
[0075] The preparation method of perovskite battery is as follows:
[0076] (1) Substrate cleaning: Place 20 pieces of 2×2 cm FTO glass on a glass stand and put them into a 400 mL beaker. Add 150 mL of detergent aqueous solution, deionized water, ethanol and isopropyl alcohol (IPA) in sequence. Perform ultrasonic cleaning at room temperature for 5 minutes each. Take them out and blow dry them with a N2 air gun. Then put them into a UVO cleaning machine and perform UVO cleaning for 30 minutes.
[0077] (2) Deposition of the first charge transport layer: The first charge transport layer was prepared by chemical bath deposition. 2.5 g urea (purity 99%) was dissolved in 200 mL deionized water, 50 μL thioglycolic acid (TGA) and 2.5 mL hydrochloric acid (37 wt%) were added, and the solution was homogenized by ultrasonication for 5 minutes, and then 0.55 g SnCl2·2H2O (purity 99.995%) was added and dissolved by ultrasonication for 2 minutes, and then the UVO-treated FTO glass was immersed in the chemical bath solution, placed in an oven, and deposited at 90°C for 5 hours. After the deposition was completed, the glass was taken out and ultrasonically cleaned with deionized water and IPA for 5 minutes respectively, and then dried with a N2 air gun, and annealed on a hot plate at 180°C for 1 hour to obtain the FTO glass with an electron transport layer.
[0078] (3) Perovskite layer deposition: The perovskite solution was obtained by dissolving 1.4 M FAI, 1.54 M PbI2, 0.5 M MACl and 0.05 M CsCl in a mixed solution of DMF:DMSO=4:1 (v:v). 120 μL of the perovskite solution was spin coated on the first charge transport layer (spin coating speed of 3000 rpm, spin coating time of 30 s, spin coating acceleration of 300 rpm / s), during which 150 μL of ethyl acetate was added dropwise, and then annealed on a hot plate at 150°C for 10 min. A hole transport layer was prepared on the surface of the electron transport layer.
[0079] (4) Deposition of the second charge transport layer: This battery is a formal battery, and the second charge transport layer is a hole transport layer. 140 mg of Spiro-OMeTAD was dissolved in 2 mL of chlorobenzene, and then 2 mg of UiO-66-2H nanoparticles were added. Ultrasonication was performed for 10 min to uniformly distribute UiO-66-2H in the Spiro-OMeTAD solution. Then, 30 μL of Li-TFSI (520 mg / mL acetonitrile), 15 μL of FK209 (375 mg / mL acetonitrile), and 50 μL of 4-tert-butylpyridine (TBP) were added to obtain a hole transport layer solution. 100 μL was spin-coated on the perovskite layer (4000 rpm, 30 s, 2000 rpm / s) to complete the deposition of the second charge transport layer.
[0080] (5) Back electrode deposition: A metal back electrode layer is deposited by magnetron sputtering or other methods. Here, an Au back electrode is used with a film thickness of 100 nm.
[0081] Comparative Example 1
[0082] Comparative Example 1 A complete perovskite battery device was prepared by referring to the preparation method of Example 1, except that the preparation method of the hole transport layer of Comparative Example 1 is as follows:
[0083] Comparative Example 1 is a formal battery prepared by dissolving 140 mg Spiro-OMeTAD in 2 mL of chlorobenzene, then adding 30 μL Li-TFSI (520 mg / mL acetonitrile), 15 μL FK209 (375 mg / mL acetonitrile), and 50 μL 4-tert-butylpyridine (TBP) to obtain a hole transport layer solution, and spin coating 100 μL on the perovskite layer. The spin coating conditions are as follows: 4000 rpm, 30 s, 2000 rpm / s, to complete the deposition of the second charge transport layer.
[0084] The hole transport layer of Comparative Example 1 does not contain the metal organic framework material UiO-66-2H nanoparticles of the present invention.
[0085] Example 2
[0086] Example 2 A complete perovskite battery device was prepared by referring to the preparation method of Example 1, but the difference is that the formula of the perovskite precursor solution of Example 2 is as follows: CsI:FAI:MAI:PbI2:PbBr2:MACl=:0.04:0.80:0.05:0.95:0.03:0.20 was dissolved in a solution of DMF:DMSO=8:1 (v:v) and mixed.
[0087] Comparative Example 2
[0088] Comparative Example 2 prepared a complete perovskite battery device by referring to the preparation method of Example 2, except that the preparation method of the hole transport layer of Comparative Example 2 referred to Comparative Example 1.
[0089] Example 3
[0090] Example 3 A complete perovskite battery device was prepared by referring to the preparation method of Example 1, but the difference is that Alfa tin oxide was used as the electron transport layer in Example 3. The specific operation was as follows: a tin (IV) oxide solution (15wt% colloidal dispersion in water) was diluted with water to a concentration of 3.0wt%, and then 100uL was spin-coated at 3000rpm for 30 seconds, and finally annealed at 150°C in ambient air for 30min.
[0091] Comparative Example 3
[0092] Comparative Example 3 prepared a complete perovskite battery device by referring to the preparation method of Example 3, except that the preparation method of the hole transport layer of Comparative Example 3 refers to Comparative Example 1, and the hole transport layer does not contain the metal organic framework material UiO-66-2H nanoparticles of the present invention.
[0093] Example 4
[0094] Example 4 refers to the preparation method of Example 1 to prepare a complete perovskite battery device, but the difference is that Example 4 uses Ag as the back electrode with a film thickness of 100 nm.
[0095] Comparative Example 4
[0096] Comparative Example 4 prepared a complete perovskite battery device by referring to the preparation method of Example 4, except that the preparation method of the hole transport layer of Comparative Example 4 refers to Comparative Example 1, and the hole transport layer does not contain the metal organic framework material UiO-66-2H nanoparticles of the present invention.
[0097] Example 5
[0098] Example 5 The metal organic framework material UiO-66-2H nanoparticles were prepared by referring to the method of Example 1, except that the amount of ZrCl4 solution added was 20 mg and the amount of 1,2,4,5-benzenetetracarboxylic acid added was 5 mg.
[0099] The UiO-66-2H nanoparticles of Example 5 were used to prepare a perovskite cell according to the preparation method of the perovskite cell of Example 1.
[0100] Example 6
[0101] Example 6 The metal organic framework material UiO-66-2H nanoparticles were prepared by referring to the method of Example 1, except that the heating reaction temperature was 120° C. and the reaction time was 12 h.
[0102] The UiO-66-2H nanoparticles of Example 6 were used to prepare a perovskite cell according to the preparation method of the perovskite cell of Example 1.
[0103] Example 7
[0104] Example 7 Metal organic framework material UiO-66-2H nanoparticles were prepared by referring to the method of Example 1, except that the amount of acetic acid added was 100 μL.
[0105] The UiO-66-2H nanoparticles of Example 7 were used to prepare a perovskite cell according to the preparation method of the perovskite cell of Example 1.
[0106] Performance Testing
[0107] 1. Observe the metal organic framework material UiO-66-2H nanoparticles prepared in Example 1 using an electron scanning electron microscope. Figure 1 As shown, the size of the prepared UiO-66-2H is 30-50 nm. A small amount is added when preparing the hole transport layer and can be evenly dispersed in the Spiro-OMeTAD solution after ultrasound.
[0108] 2. The metal organic framework material UiO-66-2H nanoparticles of Example 1 were analyzed by powder X-ray diffractometer to obtain the following Figure 2 The PXRD diffraction pattern shown is Figure 2 It can be seen that the diffraction peak of UiO-66-2H synthesized in Example 1 corresponds to the peak energy of Calculate.
[0109] 3. The performance of the perovskite battery devices prepared in Examples 1 to 7 and Comparative Example 1 was tested. The results are shown in Table 1.
[0110] The JV characterization test was performed as follows: Current density-voltage (JV) measurements were performed on a Keithley 2400 digital source meter controlled by TestPoint software under a xenon lamp. The light intensity was calibrated using an NREL-certified KG5 filtered silicon reference diode. The measurement setup was anti-reflection coated. All JV curves of the device were measured using reverse scans (from 1.20 V to 0 V) and forward scans (from 0 V to 1.2 V) at a constant scan speed of 10 mV / s.
[0111] Table 1
[0112]
[0113]
[0114] It can be seen from Table 1 that the hole transport layers of Examples 1 to 7 are all added with the UiO-66-2H nanoparticles of the present invention, and the prepared perovskite cells all obtain good photoelectric conversion efficiency and stability. In addition, Examples 1 to 4 correspond to Comparative Examples 1 to 4, which do not add the UiO-66-2H nanoparticles of the present invention, respectively. The photoelectric conversion efficiency and 7-day retention rate (%) of the perovskite cells of Examples 1 to 4 are better than those of Comparative Examples 1 to 4.
[0115] It can be seen that the present invention mixes 1,2,4,5-benzenetetracarboxylic acid and ZrCl4, adds the regulator acetic acid, can adjust the crystal growth of metal organic framework materials, prepares UiO-66-2H nanoparticles with high-density free carboxyl groups and nanostructures, and applies them to the preparation of the hole transport layer of the perovskite battery. The high-density free carboxyl groups of the UiO-66-2H nanoparticles can well adsorb lithium ions, prevent the lithium ions in the hole transport layer from migrating to the perovskite layer, and the UiO-66-2H nanoparticles can also be uniformly dispersed in the hole transport material with the help of their nano-morphology, thereby better adsorbing lithium ions in the solution. In addition, the free carboxyl groups in the UiO-66-2H nanoparticles can also form chemical bonds with the Pb ions of the perovskite active layer, reduce the surface defects and unsaturated bonds of the perovskite active layer, and prevent the recombination of electrons and holes, thereby improving the electrochemical performance and stability of the perovskite battery.
[0116] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a metal organic framework material, characterized in that: The following steps are involved: 1,2,4,5-benzenetetracarboxylic acid is dissolved in an organic solvent, ZrCl4 and a regulator acetic acid are added, and the mixture is heated for reaction to obtain a reactant, and the reactant is centrifuged, washed, and dried to obtain UiO-66-2H nanoparticles.
2. The method for preparing the metal organic framework material according to claim 1, characterized in that: The amount of the regulator acetic acid added is 20-100uL; and / or the mass ratio of the 1,2,4,5-benzenetetracarboxylic acid and ZrCl4 is (1:2) to (1:4).
3. The method for preparing the metal organic framework material according to claim 1, characterized in that: The temperature of the heating reaction is 80° C. to 120° C.; and / or the reaction time of the heating reaction is 12 h to 24 h.
4. A metal-organic framework material prepared by the method for preparing a metal-organic framework material according to any one of claims 1 to 3.
5. The metal organic framework material according to claim 4, characterized in that: The metal organic framework material includes free carboxyl groups.
6. A perovskite battery, characterized in that: The perovskite cell comprises a hole transport layer, and the hole transport layer comprises the metal organic framework material according to claim 4 or 5.
7. The perovskite cell according to claim 6, characterized in that: The perovskite cell comprises, from bottom to top, a conductive substrate, an electron transport layer, a perovskite active layer, the hole transport layer and a back electrode layer.
8. The perovskite battery according to claim 6, characterized in that: The method for preparing the hole transport layer comprises the following steps: The hole transport layer material and the metal organic framework material are mixed and dissolved to obtain a hole transport layer solution, The hole transport layer is obtained by coating the hole transport layer solution on the surface of a substrate.
9. The perovskite cell according to claim 8, characterized in that: The mass ratio of the hole transport material to the metal organic framework material is (100:1) to (50:1).
10. The perovskite cell according to claim 8, characterized in that: The hole transport layer solution further includes a dopant, and the dopant includes a lithium ion dopant.
Citation Information
Cited By
Solar cell, preparation method thereof and photovoltaic module
CN120936175A
Solar cell and method of manufacturing the same, photovoltaic module
CN120936175B
Preparation method of perovskite solar cell
CN121174889A